Protocol for isolation and proteostatic analysis of sub-populations of spermatogenic cells in mouse - Qianxing Zou; Lele Yang; Huayu Qi (STAR Protocols, 2022)
Summary: Spermatogenesis generates heterologous cell populations which, if not distinguished clearly, often hinder mechanistic and etiological studies. Here, we present a protocol to identify and isolate populations of mouse spermatogenic cells, including spermatogonial stem cells (SSCs), spermatocytes, and haploid spermatids. We also describe absolute quantification of mRNA copy numbers in SSCs. The isolated cells can be used for analyzing nascent protein synthesis and protein degradation, two main events that maintain cellular proteostasis important for healthy and long-term production of male gametes.For complete details on the use and execution of this protocol, please refer to Zou et al. (2021). : Publisher's note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.